Remaking the past: Musical modernism and the influence of the tonal tradition - Straus, Joseph N. (Cambridge Harvard university press, 1990)
Joseph Straus details the revisionary strategies of twentieth century composers--how they transformed the music of the tonal tradition in creating their radically new sonorities and structures. He defines a mainstream of musical modernism, a mainstream shaped by the aggressive reinterpretation of eighteenth- and nineteenth-century models.